MEMBANGUN KECERDASAN SOSIAL EMOSIONAL ANAK USIA DINI MELALUI PENDEKATAN ISLAMI - Risma Yuliawati; Sri Wahyuni (Program Studi Pendidikan Islam Anak Usia Dini, 2025)
The development of social-emotional intelligence in early childhood is a vital foundation for shaping a child’s character and personality in the future. Children with social-emotional intelligence are able to recognize and manage their emotions, build positive relationship with others, and demonstrate emphaty and social responsibility. In the context of Islamic Eraly Childhood Education (PIAUD), an Islamic approach can serve as a strong basis for nurturing social-emotional values from an early age. This article discusses how Islamic values are integrated into learning activities in early childhood eduvcation institutions. Teachings of Islam- such as compassion, emphaty, patience, and helping others-are implemented in various learning activities in PIAUD institutions. This research employs a qualitative approach using a library-based case study method as the primary rechnique. The results show that the Islamic approach not only supports the development of children’s social-emotional skills but also strengthens the formation of noble character from an early age. This article is expected to serve as a reference for teacher and prospective educators in designing learning that supports the holistic development of childen’s social-emotional competencies based on Islamics values.